Burns in Israel, comparative study: Demographic, etiologic and clinical trends 1997–2003 vs. 2004–2010. Issue 3 (May 2016) - Harats, M.; Peleg, K.; Givon, A.; Kornhaber, R.; Goder, M.; Jaeger, M.; Haik, J.
Highlights: Five burn units strategically located in Israel in an area of 20, 770 km 2 . Recent disasters require re-evaluation of burns admitted to Israeli burn units. At high risk are infants under two years of age, males and non-Jewish populations. Target populations and trends of burns were identified. Prevention programmes and policies developed according to the data. Abstract: Objectives: To review hospitalised burn patients from 2004 to 2010 admitted to Israeli burn units and compare these result with data from 1997 to 2003. Methods: Retrospectively, data was collected from the Israeli Trauma Registry (ITR) encompassing all burn admissions to Israeli burn units from 2004–2010 and compared to 1997–2003. Results: Of the 5269 burn patients admitted from 2004 to 2010, 39.8% were non-Jewish. Infants under two years were the prominent age group (24.1%). Second to third degree burns 1–9% TBSA/first degree burns were 71%, second to third degree burns 10–19% TBSA were 16% and those 20% > TBSA consisted of 13%. Only 2.7% involved an inhalation injury. The average length of stay was 11.67 days and mortality rate 3.72%. All data was compared to the previous year's 1997–2003 and trends were identified. Conclusions: Within Israel, high risk populations remain infants under two years of age, males and those from non-Jewish populations. National prevention strategies and campaigns are warranted to inform and educated parents of young children and those at risk of burns. Of note, advances in burn care and procedures might have contributed to a decrease in the length of hospital stay (LOS).